Negative Impoliteness and Reconstruction of Identity: Cyberpragmatics Analysis of Palestinian Conflict News Comments on Arab Youtube Channel - Yufni Faisol; Wahyudi Rahmat (Masyarakat Linguistik Indonesia Universitas Andalas, 2021)
This study aims to explain the negative impoliteness in the comments on the news of the Palestinian conflict on the Arab Youtube channel. This descriptive qualitative research took the source of data in the form of 5 news of the attack on the Al-Aqsa mosque complex by the Israeli military on the Al Jazeera youtube channel as a data source. The internet archive documentation technique and free-of-conversation listening technique were used at the data collection stage. Meanwhile, the identity method by referring to the stages of qualitative analysis was used as a guide in data analysis. The researchers found 310 negative impoliteness speeches consisting of 5 types: frighten found at 17 speeches (6%); condescend, scorn or ridicule at 113 speeches (36%); invade the other's space at 72 speeches (23%); explicitly associate the others with negative aspect at 97 speeches (31%); put the other's indebtedness on record at 11 speeches (4%). The negative impoliteness has a context in the form of criticism of the political policies of Arab countries in responding to the Palestinian conflict. Speakers seek to construct a new community identity for Arab countries in the context of fighting against the Israeli occupation of Palestine. Â